Theory, Gender and Corporate Law - Katherine Hall (Legal Education Review)
Explicitly teaching theory is vital to all areas of law. Theory, whether in the general sense of jurisprudential, philosophical or political theories or in the more specific sense of theoretical analysis of particular areas of law, is an integral part of law and learning. It is as vital to learning as air is to breathing. And we usually take them for granted in much the same way. The purpose of this paper is to emphasise the importance of explicitly teaching theory in corporate law. Traditionally, corporate law has been taught without much reflection upon theory. Perhaps this has been because of the growing scope and complexity of corporate law statutes, because of the technical nature of many corporate law concepts, or because the doctrinal, procedural and practical dimensions of the topic have been considered more important than the theoretical ones. Perhaps it has just been an issue of time and space within corporate law courses and of the significant demands already placed upon corporate law lecturers in teaching such a vast area of law. But whatever the reason, the fact remains that theorising about corporate law, either generally or specifically, has not only been a neglected area of legal scholarship but also a neglected area of teaching.